La psichiatria nel nazionalsocialismo: memoria e responsabilità. Intervento in occasione della commemorazione delle vittime da parte della Società tedesca di psichiatria e psicoterapia - Schneider, Frank (Il sogno della farfalla, 2014)
On 26th November 2010, the German Association for Psychiatry and Psychotherapy (DGPPN) held a commemorative event to honour the memory of those who suffered through one of the darkest chapters in the history of the discipline. In his talk the then President of the DGPPN Prof. Frank Schneider reconstructed how under National Socialism, many psychiatrists were forced to emigrate and hundreds of thousands of psychiatric patients were the victims of unethical research, forced sterilisation and murder. The DGPPN nominated an independent Commission made up of eminent historians, called in to carefully examine both the period of National Socialism and the way German psychiatry behaved in the post war period. As President of the DGPPN, Prof. Schneider asked victims and their families for forgiveness for the pain and injustice they endured in the name of German psychiatry and at the hands of German psychiatrists.